Admission interleukin-6 and carbapenemase carriage independently predict 30-day mortality in female Fournier's gangrene: a multicenter cohort - Rini Kuswohadi Pramono; Tanvir Ahmed; Annisa (Sriwijaya Journal of Obstetrics and Gynecology, 2026)
Background: Female Fournier's gangrene (FG) is an underrecognized obstetric and gynecologic infectious emergency that frequently arises from vulvar, Bartholin gland, and episiotomy-related sources and carries high mortality. Rising multidrug resistance threatens standard empirical antibiotic regimens, yet female-specific data integrating inflammatory biomarkers with the genomic resistome are scarce. Objective: To identify independent predictors of 30-day mortality and characterize the genomic resistome in women with FG to inform targeted broad-spectrum therapy. Methods: In this multicenter retrospective cohort at two tertiary referral hospitals in Palembang, Indonesia (January 2020–December 2025), 42 women with surgically confirmed FG were studied. Admission interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-α), procalcitonin (PCT), and C-reactive protein (CRP) were measured; deep-tissue isolates underwent culture, broth-microdilution MIC testing, and multiplex PCR/next-generation sequencing for resistance genes. Multivariable logistic regression, ROC analysis, and Kaplan-Meier/Cox modeling were performed. Results: Thirty-day mortality was 26.2% (95% CI 15.3–41.1), and infections were polymicrobial in 85.7%. Non-survivors had markedly higher admission IL-6 (485.2 vs 142.5 pg/mL; p<0.001; Cohen's d=2.58) and PCT (18.6 vs 4.2 ng/mL; p<0.001). IL-6 predicted mortality with an AUC of 0.93 (95% CI 0.83–0.99), outperforming LRINEC (AUC 0.69). Independent predictors were carbapenemase-producing isolates (adjusted OR 4.15, 95% CI 1.85–9.20; p=0.001) and admission IL-6 ≥300 pg/mL (adjusted OR 3.80, 95% CI 1.62–8.85; p=0.002). Resistome-concordant empirical therapy was associated with lower mortality (modeled NNT 3). Conclusion: Admission IL-6 and carbapenemase carriage independently predicted 30-day mortality in this female FG cohort. Rapid biomarker and resistome screening may support risk stratification and empirical coverage in high-resistance tertiary settings, but prospective external validation is required before practice adoption.